Repetitive bout of controlled soccer heading does not alter heart rate variability metrics: A preliminary investigation - Smirl, Jonathan David; Peacock, Dakota; Burma, Joel Stephen; Wright, Alexander D.; Bouliane, Kevin J.; Dierijck, Jill; van Donkelaar, Paul (Frontiers in Neurology, 2022)
Objectives: There is elevated unease regarding how repetitive head impacts, such as those associated with soccer heading, contribute to alterations in brain function. This study examined the extent heart rate variability (HRV) and cardiac baroreceptor sensitivity (BRS) metrics are altered immediately following an acute bout of soccer heading. Methods: Seven male elite soccer players (24.1±1.5 years) completed 40 successful soccer headers in 20-minutes. The headers were performed under controlled circumstances using a soccer ball launcher located 25 meters away and using an initial ball velocity of 77.5±3.7 km/h (heading condition). An accelerometer (xPatch) on the right mastoid process quantified linear/rotational head accelerations. Participants also completed sham (body contact) and control (non-contact) sessions. A three-lead ECG and finger photoplethysmography characterized short-term spontaneous HRV/cardiac BRS, before and after each condition. The SCAT3 indexed symptom scores pre-post exposures to all three conditions. Results: During the heading condition, cumulative linear and rotational accelerations experienced were 1,57497.9g and 313,761±23,966rad/s2, respectively. Heart rate trended towards an increase from pre- to post-heading (p=0.063), however HRV metrics in the time-domain (ps>0.260) and frequency-domain (ps>0.327) as well as cardiac BRS (ps>0.144) were not significantly changed following all three conditions. Following the heading condition, SCAT3 symptom severity increased (p=0.030) with a trend for symptom score augmentation (p=0.078) compared to control and sham. Conclusion: Whereas symptoms as measured by the SCAT3 were induced following an acute bout of controlled soccer heading, these preliminary findings indicate they were not accompanied by alterations to autonomic function. Ultimately, this demonstrates further research is needed to understand the physiological underpinnings of alterations in brain function occurring immediately after a bout of soccer heading and how these may, over time, contribute to long-term neurological impairments.